Qiwāmah And Epistemic Violence: A Critical Socio-Legal Analysis of Gendered Authority In Islamic Family Law - Al Fiqri Ardiansyah; Marhamah Annazah Tambunan; Randy Putra Alamsyah; Idrus Afandi Akbar; Nuruddin Nuruddin (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
The concept of qiwāmah (male authority) in Q.4:34 remains a central yet contested foundation in Islamic family law, particularly in shaping gender roles and marital authority. While classical and modern tafsir have largely legitimized male leadership, existing scholarship tends to focus on reinterpretation or normative critique, leaving a gap in examining the epistemological structures that produce and sustain patriarchal authority. This study investigates qiwāmah as a site of epistemic violence and analyzes how gendered authority is constructed within Qur’anic exegesis and institutionalized in Islamic family law, particularly in the Indonesian Kompilasi Hukum Islam (KHI). Employing a qualitative approach grounded in critical hermeneutics and socio-legal analysis, the study examines classical, modern, and critical tafsir alongside legal documents. The findings demonstrate that qiwāmah is not a fixed theological doctrine but an epistemic construct shaped through interpretive traditions, juristic reasoning, and legal institutionalization. Patriarchal interpretations are reproduced through the nafaqah ṭā‘ah framework and codified in legal systems, while marginalizing alternative perspectives. This study’s specific contribution lies in advancing epistemic violence as an analytical tool in Qur’anic exegesis, shifting analysis from textual meaning to the structures of knowledge production that sustain legal authority. It further provides a framework for Islamic legal reform, emphasizing the need to reinterpret qiwāmah in light of maqāṣid al-sharī‘ah, particularly justice and human dignity.